Scrub septicemia progressing to polyneuropathy: a case report - Dr. Pradeep Kumar Jena; Dr. Swasthi Kabi Satapathy; Dr. Alok Satya Prakash Nayak; Dr. Sarthak NaIik; Dr. Mangal Charan Murmu (Pediatric Review: International Journal of Pediatric Research, 2021)
Scrub typhus is a major public health problem in India with a wide spectrum of clinical manifestations and a low index of suspicion is low endemic areas which in turn can increase morbidity and mortality. The clinical manifestations of scrub typhus can range from mild non-specific febrile illness or constitutional symptoms such as fever, rash, myalgia, headache to various organ dysfunction such as AKI, myocarditis, pneumonia, meningitis, encephalitis, GI bleed, hepatitis. Here we report a case of a 9-year-old girl who presented with scrub septicemia and progressed to develop critical illness myopathy, which is very unusual.